From medical data to simple virtual mock-up of scapulo-humeral joint - Atmani, Hakim; Mérienne, Frédéric; Fofi, David (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2009)
The surgical operations of shoulder joint are guided by various principles: osteosynthesis in the case of fracture, osteotomy in order to correct a deformation or to modify the functioning of the joint, or implementation of articular prosthesis. At the end of the twentieth century, many innovations in the domains of biomechanics and orthopedic surgery have been performed. Nevertheless, theoretical and practical problems may appear during the operation (visual field of surgeon is very limited, quality and shape of the bone is variable depending on the patient). Biomechanical criteria of success are defined for each intervention. For example, the installation with success of prosthetic implant will be estimated according to the degree of mobility of the new articulation, the movements of this articulation being function of the shape of the prosthesis and of its position on its osseous support. It is not always easy to optimize the preparation of the surgical operation for every patient, and a preliminary computer simulation would allow helping the surgeon in its choices and its preparation of the intervention. The techniques of virtual reality allow a high degree of immersion and allow envisaging the development of a navigation device during the operating act.